Small buddy balloon catheter technique facilitates deliverability of other balloons or stents in challenging cases - Iwańczyk, Sylwia; Skorupski, Wojciech J.; Grajek, Stefan; Kałużna-Oleksy, Marta; B. Lesiak, Michał; Lesiak, Maciej; Grygier, Marek (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
Despite improvements in balloon and stent technology, percutaneous coronary intervention (PCI) in calcified, tortuous, angulated or previously stented vessels is still a therapeutic challenge. The proper preparation of the vessel, confirmed by the smooth passage of smaller balloon catheters, often remains insufficient to deliver a larger, stiffer balloon or stent catheter in place of the target lesion. We describe a modified buddy balloon catheter technique that facilitates the deliverability of larger balloons or stents to these challenging lesions when the routinely used buddy wire technique as the first step fails. The small buddy balloon catheter technique is a simple extension of the buddy wire technique in which a small monorail uninflated balloon, of up to 1.5 mm, is positioned on the buddy wire distally or at the point where the balloon/stent becomes stuck. The small buddy balloon catheter appears to reduce the resistance of the rough surface, especially the angulated segment of the vessel, and facilitates other balloon or stent catheter passage. This does not concern a balloon inflation but rather catheter shaft properties. Since that technique is used in our high-volume catheterization laboratory with a surprisingly high success rate we think that it is worth sharing our experience with other operators. Consequently, we have decided to present these 2 cases.